Serum Lactate Dehydrogenase as a Prognostic Marker of Childhood Acute Lymphoblastic Leukemia - Hafiz, MG; Rahman, MM; Mannan, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):169-73. The abstract of this article is available on the PubMed website